Deciphering excited state properties utilizing algebraic diagrammatic construction schemes of decreasing order - Hoffmann, Marvin; Dreuw, Andreas (Journal of computational chemistry, 2021)
Excited state properties are difficult to trace back to the common molecular orbital picture when the excited state wavefunction is a linear combination of two or more Slater determinants. Here, a theoretical methodology is introduced based on the algebraic diagrammatic construction scheme for the polarization propagator (ADC(n)) that allows to make this connection and to eventually derive structure-function relationships. The usefulness of this approach is demonstrated by an analysis of the transition dipole moments of the low-lying 1B3u and 2B3u states of anthracene and (1,4,5,8)-tetraazaanthracene.
Gesehen am 04.01.2022